2009
DOI: 10.1016/j.tox.2008.10.020
|View full text |Cite
|
Sign up to set email alerts
|

CYP2E1 overexpression inhibits microsomal Ca2+-ATPase activity in HepG2 cells

Abstract: Cytochrome P450 2E1 (CYP2E1) is a microsomal enzyme that generates reactive oxygen species during its catalytic cycle. We previously found an important role for calcium in CYP2E1-potentiated injury in HepG2 cells. The possibility that CYP2E1 may oxidatively damage and inactivate the microsomal Ca 2+ -ATPase in intact liver cells was evaluated, in order to explain why calcium is elevated during CYP2E1 toxicity. Microsomes were isolated by differential centrifugation from two liver cells lines: E47 cells (HepG2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The contrasted results observed for these two compounds (Table I) suggest that this difference lies in the cell's metabolic capability. While CPA's genotoxicity for HepG2 cells has previously been reported [Westerink et al, 2011;Tsamou et al, 2012], the genotoxic potential of DMNA for these cells without the addition of a bioactivation system has not been demonstrated [Westerink et al, 2007b;Tsamou et al, 2012], probably due to poor CYP2E1 expression in this cell line [Caro et al, 2009]. Our results for the five other compounds (BaP, DMBA, AFB1, 2-AAF, and DAT), which share a genotoxic MOA related to a specific biotransformation process, confirmed that HepG2 cells express functional CYP1A1, 1A2, 1B1, and 3A4 activities.…”
Section: Discussionmentioning
confidence: 76%
“…The contrasted results observed for these two compounds (Table I) suggest that this difference lies in the cell's metabolic capability. While CPA's genotoxicity for HepG2 cells has previously been reported [Westerink et al, 2011;Tsamou et al, 2012], the genotoxic potential of DMNA for these cells without the addition of a bioactivation system has not been demonstrated [Westerink et al, 2007b;Tsamou et al, 2012], probably due to poor CYP2E1 expression in this cell line [Caro et al, 2009]. Our results for the five other compounds (BaP, DMBA, AFB1, 2-AAF, and DAT), which share a genotoxic MOA related to a specific biotransformation process, confirmed that HepG2 cells express functional CYP1A1, 1A2, 1B1, and 3A4 activities.…”
Section: Discussionmentioning
confidence: 76%
“…The intensity of chemiluminescent protein bands was visualized by fluorography on X-ray film and was scanned, and the protein bands were quantified by densitometry. All assays were performed within a linear range, and bands' intensities were normalized to G␤, a loading control for microsomal samples (Caro et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…CYP2E1 is believed to contribute to alcoholic liver disease and nonalcoholic steatohepatitis through effects on lipid hydroperoxides [127129]. There is a great deal of in vitro evidence to suggest that induction of CYP2E1 in cultured cell systems results in oxidative damage to the cells [130132]. There is also accumulating in vivo evidence to suggest that CYP2E1 plays a role in alcohol-mediated liver injury [114].…”
Section: Physiological Significance Of Cyp Targeted To Mitochondrimentioning
confidence: 99%